(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Transgender individuals face disproportionately high rates of sexual violence, yet their needs remain inadequately addressed within conventional forensic and medico-legal systems. This review explores the unique vulnerabilities of transgender survivors of sexual assault and critically examines the challenges they face during medicolegal examina tions. While global data reveal alarming levels of victimization, structural barriers – including stigma, misgendering, and binary-centric protocols – discourage reporting and impede access to justice and healthcare. In India, despite progressive legal reforms such as the Transgender Persons (Protection of Rights) Act, 2019 and the NALSA judgment, forensic pro tocols and documentation formats continue to rely heavily on binary gender frameworks, leaving transgender survivors marginalized within legal and medical settings. The review synthesizes existing international and national guidelines, identifying key gaps and proposing best practices for inclusive, trauma-informed, and gender-affirming forensic care. It emphasizes the ethical obligations of healthcare professionals to uphold autonomy, non-maleficence, beneficence, and justice in their approach. The need for sensitization training, inclusive infrastructure, respectful documentation, and integrated mental health support is underscored. Furthermore, the paper outlines specific procedural adaptations that can improve forensic outcomes and reduce re-traumatization. This review identifies gaps in current forensic procedures and outlines practical measures needed for accurate, respectful, and legally acceptable examination of transgender survi vors. By adopting affirming and inclusive approaches, healthcare and legal professionals can help ensure that transgender survivors of sexual violence receive the dignity, care, and justice they are entitled to.